A MODELING STUDY ON HYDROLYSIS OF LACTOSE RECOVERED FROM WHEY AND -GALACTOSIDASE STABILITY UNDER SONIC TREATMENT - Demirhan, Elcin; Ozbek, Belma (TAYLOR & FRANCIS INC, 2009)
In the present study, the aim was to investigate the effect of ultrasonication on the kinetics of hydrolysis of lactose recovered from whey. The effects of the duty cycle, acoustic power of sonifier, reaction volume, and the hydrolysis products on hydrolysis degree as well as on enzyme stability were studied. The hydrolysis reactions were carried out in 25mM phosphate buffer solution by using a commercial -galactosidase produced from Kluyveromyces marxianus lactis under the conditions of 37C, pH6.5, and processing time of 30min. Under ultrasonic treatment, 92% of lactose charged was hydrolyzed and the residual enzyme activity was 77% under the optimum operational conditions: acoustic power of 20W, duty cycle rate of 10%, and reaction volume of 250mL. The corresponding values of hydrolysis degree and residual enzyme activity without ultrasonic irradiation were 81% and 68%, respectively. These results show that sonication was beneficial for hydrolysis of lactose recovered from whey. The mathematical models were derived by using the experimental data of residual lactose concentration and residual enzyme activity depending on the operating conditions. In addition, an exponential equation was used for reflecting the ultrasonic energy regarding the hydrolysis and enzyme inactivation. After evaluation of the data, the activation energy required for hydrolysis of lactose recovered from whey (EH) and the inactivation energy for -galactosidase enzyme (ED) were found as 0.0489 and 0.0804JmL-1, respectively.
Keywords: -Galactosidase; Acoustic power; Duty cycle; Hydrolysis; Modeling; Volume; Whey lactose; IMMOBILIZED BETA-GALACTOSIDASE; KLUYVEROMYCES-FRAGILIS; STARCH HYDROLYSIS; ESCHERICHIA-COLI; ULTRASOUND; INACTIVATION; INHIBITION; SUPPORTS; PERMEATE; KINETICS; Engineering